EFEKTIVITAS PENDEKATAN ETNOSAINS DALAM PEMBELAJARAN DARING UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR SISWA MATERI KALOR - Zainatul Khoiriyah; Dyah astriani; Ahmad Qosyim (PENSA: E-JURNAL PENDIDIKAN SAINS, 2021)
The research was conducted to determine the effectiveness of ethnoscience approach in online learning to improve students' motivation and learning outcomes. The subjects in the study were VII A class as an experimental class and VII C class as a control class at SMPN 33 Surabaya. The research design that had been used was quantitative with pretest-posttest control group that has experimental group and control group. The implementation of learning was measured by the data of learning readiness observation homework. The collection of student motivation data using ARCS questionnaire techniques. Student learning results were obtained from the calculation of pretest-posttest scores that had been analyzed through independent t-tests and N-gain. The results of the implementation of learning had shown the experimental class had better implementation than the control class. Motivational analysis obtained had shown the experimental class had a higher motivation in each indicator compared to the control class. Student learning outcomes from an independent sample t-test analysis had shown a probability of 0.001, so there was a significant difference between experimental class learning outcomes and control classes. The average N-gain of experimental graders was 0.71 in the high category, while the control class was 0.40 in the low category. The overall results of the analysis had shown that online learning with an ethnoscience approach was effective for improving students' motivation and learning outcomes. As a research application of learning approach, this article can be a reference for the application of ethnoscience approach in learning by teachers and can be used as a literature study for further research in the field of education.